Self-Efficacy and Perceived Organizational Support as Predictors of Job Satisfaction: The Mediating Role of Pay Satisfaction. SEM Analysis - Cocić, Nikola Z. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
This study examines the relationship between self-efficacy, perceived organizational support, and job satisfaction, with pay satisfaction as a mediator. The sample is convenient and consists of 269 respondents (139 male and 136 female), aged 19 to 43 (M = 25.8, Sd = 4.3), working in an organizational or industrial environment. Out of the 269 respondents, 223 indicated their monthly income was average, 45 reported it as above average, and 1 stated it was below average. The instruments used for data collection were Minnesota Satisfaction Questionnaire (MSQ), General Self-Efficacy Scale (GSE), Perceived Organizational Support Scale, and respondents’ pay satisfaction was assessed using a single question. A statistically significant correlation was found between all the variables included in the study (p < 0.01). Pay satisfaction had a mediating influence on the relationship between self-efficacy and job satisfaction, while perceived organizational support was a direct, statistically significant predictor of job satisfaction. The model proved to be sustainable. The study results are discussed in relation to relevant theoretical assumptions and their practical applications. The limitations of the study, such as sample adequacy, online administration, and the work environments, are stated. Recommendations are made for further research, including the exploration of additional variables to enhance the current model.